Echocardiographic assessment of left ventricular filling after mitral valve surgery. Issue 12 (December 1977) - St John Sutton, M G; Traill, T A; Ghafour, A S; Brown, D J; Gibson, D G
Abstract : In order to investigate the functional effects of mitral valve surgery, echocardiograms showing left ventricular dimension were recorded and digitised in 14 normal subjects and 129 patients after mitral valve surgery. Measurements were made of peak rate of increase of dimension (dD/dt) and duration of rapid filling, studies on left ventriculograms in 36 patients having shown close correlation between these values and changes in cavity volume. In 14 patients with mitral stenosis, peak dD/dt was reduced to 7-2 +/ 1-5 cm/s, and filling period prolonged to 330 +/- 65 ms, compared with normal (16-0 +/- 3-2 cm/s, and 160 +/- 50 ms, respectively), and after mitral valvotomy, these values improved significantly (10-4 +/- 2-7 cm/s and 245 +/- 55 ms). Characteristic abnormalities were found in 67 patients with mitral prostheses. Values for the Björk-Shiley (10-5 +/- 4-2 cm/s and 180 +/- 80 ms) and Hancock (10-3 +/- 3-7 cm/s, 245 +/- 80 ms) values were similar, and both superior to the Starr-Edwards (7-4 +/- 3-0 cm/s, 295 +/- 105 ms). Results after mitral valve repair in 30 cases were not significantly different from normal (14-4 +/- 5-0 cm/s, 170 +/- 50 ms). Values outside the 95 per cent confidence limits for the valve in question allowed diagnosis of value malfunction in 18 cases. The method is value in comparing different operative procedures and in following up patients after mitral valve surgery.